P16: cycling off the beaten path. (2nd November 2019) - Buj, Raquel; Aird, Katherine M.
ABSTRACT: p16 INK4A (hereafter called p16) is a faithful cellular ally in the fight against tumorigenesis. Although its canonical pathway through retinoblastoma (RB) is well delineated, RB-independent functions for p16 are beginning to emerge. Here we summarize non-canonical roles of p16, including our recent finding on its role in nucleotide metabolism.